Early Detection of Pregnant Women with Stunting Incidents Based on the Early Detection Information System, High Risk, Islands Maternal Referral System (SIDILAN)” - Liana Devi Oktavia; Astri Yulia Sari Lubis; Susan Delilah; Darwitri Darwitri; Nurul Aini Suria Saputri (Indonesian Journal of Global Health Research, 2024)
One of the nutritional issues that toddlers face in today's society is the prevalence of short toddlers, often known as stunting. South Asia accounted for the biggest percentage of Asia's 83.6 million stunted toddlers (58.7%), while Central Asia had the lowest percentage (0.9%). The urgency of this research is the high number of stunting cases in Indonesia, where various risk factors for stunting since pregnancy are one of the focus problems that need to be considered. This study aims to determine the risk of stunting early in pregnant women through the SIDILAN early detection application. FGD and preliminary research are the first steps in the process, after which an application feasibility test is conducted. small sample user trials, followed by a quasi-experiment (pre-test post-test approach) to conduct further study. Pregnant Women with Stunting Incidents: An Early Detection Application Based on the High-Risk Early Detection Information System for Pregnant Women Referral System for the Islands (SDILAN) is an effective early detection tool for stunting in pregnant women, as shown by the p value = 0.000 from table 3 above which is smaller. Application SDILAN is thought to be more successful for monitoring and planning pregnant women because it can be completed anywhere and offers direct guidance from medical professionals. In the area of maternity and child health technology, this is also consistent with the medium-term development goals, which place an emphasis on early identification to deliver high-quality services to lower morbidity and mortality.